A new species of Neoroussoella peltophora in Roussoellaceae, from Thailand - Pasouvang, Pahoua; Karunarathna, Anuruddha; de Silva, Nimali Indeewari; Sibounnavong, Phoutthasone; Zhao, Haijun; Luo, Mei; Jayawardena, Ruvishika S. (Phytotaxa, 2022)
In this study, we introduce an asexual morph of a novel species Neoroussoella peltophora (Roussoellaceae) on Peltophorum vogelianum (Fabaceae) collected from Chiang Rai Province, Thailand. Morphologically the new species resembles Neoroussoella species. Phylogenetic analyses of concatenated LSU, SSU, ITS, tef1-α and rpb2 sequence data revealed that (MFLU 21–0113) is phylogenetically distinct (91% MLBS/1.00 BYPP). Neoroussoella peltophora differs from N. fulvicomae in having thinner peridium and differs from N. alishanense in having thicker peridium. Further, N. peltophora is distinct from N. alishanense in having shorter conidiogenous cells and differs from N. fulvicomae in having longer conidiogenous cells. The base pair comparison of ITS, tef1-α and rpb2 gene regions also support that our isolate is distinctive from the other species in Neoroussoella.